Determinants of Financial Distress in Non-Financial State-Owned Enterprises in Indonesia - Maura, Ikrana Shafa; Fajri, Mega Barokatul; Hakim, Adi Lukman (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The study aims to assess how liquidity, profitability, leverage, capital structure, and the audit committee influence the financial challenges faced by State-Owned Enterprises (SOEs). The research employs a purposive sampling method based on specific criteria, with 20 companies included in the study. The multiple linear correlation test reveals a strong relationship between liquidity, profitability, and company size regarding financial challenges. Analysis conducted using SPSS software indicates a significance value for the F-test, suggesting that liquidity, profitability, leverage, capital structure, and the audit committee significantly impact the financial difficulties. Furthermore, the t-test results demonstrate that liquidity, profitability, leverage, and capital structure play a role in influencing the financial challenges, whereas the audit committee does not have a significant effect.